Analisis Studi Kelayakan Bisnis UMKM “Awas Pancong” - Nabila Rinty Mafasy; Nanda Puteri; Tia Firnanda; Kuny Mufida; Nisrina Rizqy Kamilah; Valentina Br Sagala; Nahrudi Nahrudi; M. Avan Dwi Adi Nur Kholiq; Oryza Ardhiarisca (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the feasibility of the culinary business “Awas Pancong” as an innovation of traditional food with a modern concept. The research employs a descriptive qualitative method using observation, interviews, and literature review, with analysis covering market, management, financial, and SWOT aspects. The results indicate that the business has strong market potential, particularly among students and the general public. Financial analysis shows an R/C ratio of 1.0216 and a Return on Investment (ROI) of 10%, indicating that the business is feasible, with a payback period of 2.22 years. The SWOT analysis highlights strengths in affordable raw materials and pricing, opportunities from modern culinary trends, as well as weaknesses in product durability and threats from competition.